Clinical Cholera Surveillance Sensitivity in Bangladesh and Implications for Large-Scale Disease Control. (28th August 2021) - Hegde, Sonia T; Lee, Elizabeth C; Islam Khan, Ashraful; Lauer, Stephen A; Islam, Md Taufiqul; Rahman Bhuiyan, Taufiqur; Lessler, Justin; Azman, Andrew S; Qadri, Firdausi; Gurley, Emily S
Abstract: Background: A surveillance system that is sensitive to detecting high burden areas is critical for achieving widespread disease control. In 2014, Bangladesh established a nationwide, facility-based cholera surveillance system for Vibrio cholerae infection. We sought to measure the sensitivity of this surveillance system to detect cases to assess whether cholera elimination targets outlined by the Bangladesh national control plan can be adequately measured. Methods: We overlaid maps of nationally representative annual V cholerae seroincidence onto maps of the catchment areas of facilities where confirmatory laboratory testing for cholera was conducted, and we identified its spatial complement as surveillance greyspots, areas where cases likely occur but go undetected. We assessed surveillance system sensitivity and changes to sensitivity given alternate surveillance site selection strategies. Results: We estimated that 69% of Bangladeshis (111.7 million individuals) live in surveillance greyspots and that 23% (25.5 million) of these individuals live in areas with the highest V cholerae infection rates. Conclusions: The cholera surveillance system in Bangladesh has the ability to monitor progress towards cholera elimination goals among 31% of the country's population, which may be insufficient for accurately measuring progress. Increasing surveillance coverage, particularly in the highest risk areas, should be considered.